SIBLINGS A Server Framework for the Platform-Adaptive Delivery of Site Content - Sant, Joseph (Trinity College Dublin. Department of Computer Science, 2000)
The increasing use of devices such as connected palmtops and internet appliances has led to a need for web site designers to accommodate a wider range of client platforms and capabilities. Several approaches for transparently supporting this task have been proposed and implemented. Most assume that one site structure and navigation scheme can be appropriate for all devices and concentrate on adapting the presentation of content. This dissertation presents a server infrastructure that will support transparent adaptation of presentation while allowing for different site structures and navigation schemes.

This dissertation describes the design and implementation of a server framework based on Jigsaw's object oriented server architecture that enables the adaptive delivery of site content to diverse client platform types. The server can support the use of parallel platform specific static HTML page collections in web site authoring by dynamically selecting the pages most appropriate for the client platform. The framework was designed to be able to use current protocols and work effectively on small and medium powered servers. Most of the server enhancements are pluggable components that would facilitate the accommodation of new standards by encoding and plugging new components. It can work with traditional HTML as well as more advanced document base structures (i.e. XML for content representation and XSL style sheets to provide formatting).

The server enhancements implemented include the characterisation of user requests according to their platform type, the automatic provision of client platform information to dynamic page creation tools such as servlets, and options in server configuration to allow web masters to specify the adaptive redirection of user requests to more suitable directories, adaptive remapping of user request document names and scheduled regeneration of documents from their respective XML and XSL source. A sample web site involving different navigation and presentation approaches for desktop and palmtop clients is implemented using the server.
Keywords: Computer Science